BISPHENOL A INHIBITS DUODENAL MOVEMENT IN RAT BY INCREASING ACETYLCHOLINESTERASE ACTIVITY AND DECREASING AVAILABILITY OF FREE Ca2+IN SMOOTH MUSCLE CELLS. - KAUSHIK SARKAR; PANCHALI TARAFDER; PARTHA P. NATH; GOUTAM PAUL (International Journal of Pharma and Bio Sciences, 2013)
We report here the toxic effects of Bisphenol A (BPA) on the function of duodenum in vitro of rats. We found significant depression of amplitude (in 20 days exposure groups) and frequency of contraction of duodenum (in 30 days exposure groups). We also observed a significant increase in acetylcholinesterase (AChE) activity in duodenal tissues in both the exposure periods. From this result it is suggested that BPA depresses the amplitude and frequency of duodenal movement presumably by increasing the AChE activity in the endplate membrane of smooth muscle and efferents of local Myenteric Auerbach’s plexus. Further, we observed an increase in deposition of calcium salts in Von Kossa’s stained duodenal tissue section in both BPA exposure groups. From this study it is concluded that BPA inhibits duodenal movement by increasing AChE activity at the local neuromuscular junction and decreasing the availability of free Ca2+ in smooth muscle cells and local Myenteric terminals.